(untitled) (MAUSAM, 1978)
The present study discusses the three-dimensional circulation in the region between 75°-150°E, 10°S-50°N, as well as the associated rainfall in Southern Thailand during the period from 3 to 8 January 1975. The weather system of period studied produced one of the wettest northeast monsoons ever recorded in this country, and caused widespread floods over the Southern Thailand. Synoptic investigation is described. The rainfall data and strong northeast monsoon winds are tabulated. Synoptic charts, satellite coverage and meteorological radar observations are also presented. The study found that the exceptionally heavy rain recorded in Southern Thailand during the northeast monsoon season of 1975 was caused mainly by the prolonged existence of active low cells in an area south of Southern Thailand and Malaysia bounded by latitudes 0°-9°N and by the trough at 700 mb near 85°E and 95°E over Burma and northern Bay of Bengal. Also a depression in the Andaman Sea appeared to have an important effect on intensity of rainfall. Synoptic features which show the circulation in the layer of the atmosphere below 500 mb appear to control the weather phenomena, and seem to have the most direct effect upon distribution of rainfall